Estudos fitoquímico e biológico de Pachystroma longifolium (Nees) I. M. Johnst (Euphorbiaceae) - Galvão, Dayane de Cássia (2013)
This work describes the phytochemical and biological investigations of extracts of leaves of Pachystroma longifolium; specie of the Euphorbiaceae family that doesn’t present previously published these studies. The aim was to isolate and identify secondary metabolites of this specie and, farther, to test the extracts for inhibition of tumor cells and human cathepsins. Isolated substances were tested too. Despite the large number of drugs that come on the market over the years, many of them are only small rearrangements in chemical molecules already used as drugs. So, various diseases have still ineffective therapy and the need for innovation exists. Natural products continue to be the most promising source for new drug development, due to the complexity and diversity of substances, and the great potential of an unexplored biodiversity; since many species of plants, for example, have not been studied as the case of P. longifolium to the present work. The chromatographic method led to the isolation of compounds: loliolide (1), ethyl gallate (2), gallic acid (3) and protocatechuate methyl (4). Also a-amyrin (5) ?-amyrin (6), lupeol (7) and sitosterol (8) were identified in the mixture. The crude, hexane and ethyl acetate extracts of leaves were tested against cathepsins K, L and V, while only the crude extract was tested for inhibition of tumor cells. The most satisfactory results were obtained for inhibition of cathepsin V, to which all of the extracts showed at least 50% of inhibition at concentrations of 500, 250, 125, 50 and 25 µg/mL. For the cytotoxicty assay, the crude extract, at concentration of 1 mg/mL, was considered inactive. Four isolated substances were tested against the cathepsins K, L and V, however did not show positive results.